The Two Faces of Control: Network Closure and Individual Performance among Knowledge Workers - GARGIULO, Martin (Institutional Knowledge at Singapore Management University, 2009)
This paper argues that the effect of dense social ties, or network closure, on a knowledge worker's performance depends on the predominant role this worker plays with his or her exchange partners in the relationships affected by that closure. Using data on informal exchanges among investment bankers in the equities division of a large financial services firm operating in Europe, Asia-Pacific, Africa, and the Americas in 2001, we find that network closure in relationships in which the banker acts as an acquirer of information increases his or her performance, whereas closure in relationships in which the banker acts as a provider of information decreases it. We also find that these effects are moderated by the bankers' ability to employ alternative means (such as formal authority) to induce the cooperation of exchange partners in their acquirer role, as well as by the extent to which the bankers can benefit from being free from the control of exchange partners in their provider role. Our findings highlight the two sides of the normative control associated with network closure: control benefits people when they need to induce exchange partners to behave according to their preferences, but it hurts them when it forces them to behave according to the preferences of those partners.